Acoustic Characteristics of Underwater Composite Materials at Oblique Incidence of Sound Wave. (May 2013) - Guolong, Liang; Fubin, Pang
The acoustic characteristics of composite materials with viscoelastic coatings and the structure of underwater vehicles are discussed in this paper. A typical underwater vehicle in accordance with its acoustic characteristics, can approximately be seen as an elastic shell filled with air, whose echo wave is a great threat to its safety. In this study, viscoelastic coating is introduced to reduce the reflected wave by absorbing unwanted sounds. The absorption coefficient of the composite materials at oblique incidence of sound wave is deduced, and the influencing factors of the absorption coefficient are analyzed.